(untitled) (Innovative professional education, 2022)
The work analyzes the use of project methodology in the process ofteaching English in institutions of pre-higher vocational education. A conclusion wasmade regarding the significance of the effectiveness of the project method forimproving the quality of training of junior bachelors due to the fact that this methodprovides support for a persistent interest in learning a foreign language, deepens andsystematizes students’ knowledge of the studied topic.